The Influence of Competency-Based Training and Mentoring on Career Development in PT. Quarta Medika Indonesia - Chusuma, Jales Pupita Adilla Rihan; Setiawan, Temmy; Zakiah, Zakiah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to analyze the influence of competency-based training and mentoring on employee career development at PT. Quarta Medika Indonesia. Career development is an important aspect of Human Resource Management (HRM) that supports improved employee performance, motivation, and loyalty. Training and mentoring are seen as strategies that can help employees achieve their career goals. This study uses a quantitative method with an explanatory approach. Data were collected through questionnaires distributed to employees as respondents, then analyzed using multiple linear regression to determine the relationship between the independent and dependent variables.The results of the study indicate that competency-based training has no significant effect on career development. This indicates that training is not yet fully relevant or effective in promoting employee careers. Meanwhile, mentoring has a significant effect on career development, which means that the role of mentors in providing direction, guidance, and support is very important for employee career advancement. Simultaneously, competency-based training and mentoring have a positive effect on career development with a coefficient of determination (R²) of 0.381. This means that 38.1% of the variation in career development can be explained by these two variables. This study recommends that companies improve the quality and relevance of training, and strengthen mentoring programs as part of a sustainable HR development strategy.